2020
DOI: 10.21203/rs.3.rs-73762/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-silico study of SARS-CoV-2 and SARS with special reference to intra-protein interactions, A plausible explanation for stability, divergency and severity of SARS-CoV-2

Abstract: The current nightmare for the whole world is COVID-19. The occurrence of concentrated pneumonia cases in Wuhan city, Hubei province of China was first reported on December 30, 2019. SARS-CoV first discloses in 2002, but not outspread worldwide. After 18 years, in 2020, it reemerges and outspread worldwide as SARS-CoV-2 (COVID 19), as the most treacherous virus creating disease in the world. Is it possible to create a favorable evolution within this (18 years) short time? If possible, then what are those proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The aliphatic index was 78.72, and the grand average of hydropathicity (GRAVY) was -0.392. The aliphatic index value indicates the stability of the protein even in high temperatures (Mitra et al, 2020). This data suggested that the envelope protein is very stable in body temperature.…”
Section: Tablementioning
confidence: 75%
“…The aliphatic index was 78.72, and the grand average of hydropathicity (GRAVY) was -0.392. The aliphatic index value indicates the stability of the protein even in high temperatures (Mitra et al, 2020). This data suggested that the envelope protein is very stable in body temperature.…”
Section: Tablementioning
confidence: 75%
“…It is reported that two residues are involved in the formation of aromatic-aromatic [52][53][54]. But here, we have divided this aromatic-aromatic interactions into two divisions; isolated aromatic-aromatic interactions and network aromatic-aromatic interactions.…”
Section: Evolving Of Long Network Aromatic-aromatic Interactionsmentioning
confidence: 99%
“…20 Additional insights for dealing with COVID-19 have been drawn from the 2002 SARS-CoV-1 epidemic. [20][21][22] Given the nature of this novel coronavirus, which is spread by respiratory droplet, and the aerosolgenerating nature of tracheostomy placement, especially strict precautions are recommended for COVID-19 patients requiring ventilation. 23,24 Both the American Association for the Surgery of Trauma (AAST) and the Eastern Association for the Surgery of Trauma (EAST) have posted or endorsed guidelines specific to tracheostomy in the setting of COVID-19 on their respective webpages.…”
Section: General Precautionsmentioning
confidence: 99%
“…Ideally, placement of a cuffed, non-fenestrated tracheostomy tube should be performed in a negative pressure airborne infection isolation room (AIIR); otherwise, the procedure should be done in a setting isolated for at least 3 hours to minimize transmission of aerosols. 21 Non-essential personnel and additional equipment should be accessible but not in the room where the procedure is being performed.…”
Section: Location Equipment and Techniquementioning
confidence: 99%